MOTIVASI KERJA GURU - Wilis Fitriyana; Aliman Aliman (UNIVERSITAS BENGKULU, 2019)
Abstract: the general purpose of this research was to describe the condition of teacher’s work motivation in Public Senior High School Number One of Pendopo. The specifically problems in this study are about the diligence of teachers who are motivated in doing their duty, the factors that support teacher in order to be motivated to work diligently, the factors that obstruct teachers to work well and The Principal’s efforts in increasing the teacher’s work motivation. This research uses descriptive qualitative method. Subjects in this research are the Principal, Vice Principal Areas and teachers. The data collected by using instruments such as observation, interview and documentation. Conclusions shows that teacher’s work motivation in Public Senior High School Number One of Pendopo has been done suitable with the school role and still needs some efforts to make teachers feel more comfortable while working and some developments in school facilities such as available school canteen, park area for vehicles, library, etc.Keyword: motivation, work motivation, teacher.